2011
DOI: 10.1074/jbc.m110.203679
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation in APOC3 within the C-terminal Lipid Binding Domain of Human ApoC-III Results in Impaired Assembly and Secretion of Triacylglycerol-rich Very Low Density Lipoproteins

Abstract: Hepatic assembly of triacylglycerol (TAG)-rich very low density lipoproteins (VLDL) is achieved through recruitment of bulk TAG (presumably in the form of lipid droplets within the microsomal lumen) into VLDL precursor containing apolipoprotein (apo)BHepatic assembly of very low density lipoproteins (VLDL) rich in triacylglycerol (TAG) 5 is initiated during and after translation and translocation of apolipoprotein (apo) B-100 across the endoplasmic reticulum membrane. The nascent VLDL particle is further enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 35 publications
5
72
0
Order By: Relevance
“…However, elevated plasma levels of ApoB100 and reduced triglycerides in the VLDL fraction of Arfrp1 liv Ϫ / Ϫ mice could indicate a premature release of VLDL2. ApoC3 was described to directly interact with lipids via its helix 5, thereby facilitating triglyceride incorporation into VLDLs independently of MTP activity ( 31 ). This fi nding is supported by the fact that the human ApoC3-K58E mutation located in the lipid binding domain of ApoC3 results in a marked reduction of triglycerides and VLDLs in plasma ( 32 ).…”
Section: Accumulation Of Lipids and Altered Lipid Storage In Arfrp1 Lsupporting
confidence: 58%
“…However, elevated plasma levels of ApoB100 and reduced triglycerides in the VLDL fraction of Arfrp1 liv Ϫ / Ϫ mice could indicate a premature release of VLDL2. ApoC3 was described to directly interact with lipids via its helix 5, thereby facilitating triglyceride incorporation into VLDLs independently of MTP activity ( 31 ). This fi nding is supported by the fact that the human ApoC3-K58E mutation located in the lipid binding domain of ApoC3 results in a marked reduction of triglycerides and VLDLs in plasma ( 32 ).…”
Section: Accumulation Of Lipids and Altered Lipid Storage In Arfrp1 Lsupporting
confidence: 58%
“…In two following studies, the same group showed that two naturally occurring human mutations of apoC-III, A23T and K58E, were unable to promote triglyceride incorporation during VLDL assembly (73,74). Plasma concentrations of triglycerides and apoC-III are lower in carriers of the A23T or K58E mutations (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…However, several point mutations in the amphipathic ␣ -helices of apoC-II (W26R, L72P) and apoC-III (A23T, Q23K, K58E) alter protein expression, lipid surface-binding, or function ( 20,(55)(56)(57). Since apoC-II and C-III are structurally similar to apoC-I, we speculate that altered helical content or charge in apoC-II and apoC-III point mutations may alter protein-lipid, protein-protein, or protein-enzyme interactions, thereby infl uencing the ability of these proteins to penetrate and bind to, be retained on, and regulate the fate of TAG-rich lipoproteins.…”
Section: Discussionmentioning
confidence: 99%